The Kuznets-Kaldor-Puzzle and Neutral Cross-Capital-Intensity Structural Change - Denis Stijepic; Wagner Helmut (Verein für Socialpolitik, 2010)
The Kuznets-Kaldor stylized facts are one of the most striking empirical observations about the development process in the industrialized countries: While massive factor reallocation across technologically distinct sectors takes place, the aggregate ratios of the economy are quite stable. This implies that cross-technology factor reallocation has a relatively weak impact on the aggregates, which is a puzzle from a theoretical point of view. We provide a model that can explain this puzzle. Furthermore, we show by empirical evidence that this model is in line with 55% of structural change.
Keywords: O14; O41; D11; 330; neoclassical growth models; balanced growth; structural change; Kaldor facts; labor reallocation across sectors; sector technology